Efforts to Develop Religiosity of State Civil Apparatus through Religious Development in Karanganyar District - Muhammad Ja'far Nashir (Universitas Muhammadiyah Enrekang, 2023)
This paper aim For explain about development religiosity apparatus State Civil through Assembly Taklim Nurul Iman in the district The most important essay related with create and develop attitude ASN religiosity . Study This generate (1) Condition Religiosity Apparatus State Civil in the District Karanganyar , in general, shows that the social picture of the people of Karanganyar Regency is a plural society, socially, economically and politically very stable . And conditions bureaucracy themselves in general in the district Karanganyar show harmony between superiors and subordinates in the environment office district government So is the Regent in a manner routine give briefing to employee from class on to the very bottom that is done a month once. Besides that, reason Regent fostering religiosity the namely, the Regent want to invite For more fear to Almighty God. (2) Development Religiosity for apparatus State Civil through Assembly Taklim Nurul Iman in the District karanayar followed by all civil servants walk with fine and smooth . Proved with increase faith and piety civil servants in the neighborhood work and society , so matter This impact on the concession socio-cultural public towards. Spirit from religiosity development by praying appropriate time and community is for more civil servants discipline.